SISTEM KONTROL PEMANTAU KEBERSIHAN PENDINGIN UDARA BERBASIS MIKROKONTROLLER NODEMCU ESP-32 - Muhammad Nuryan Pratama; Ratna Atika; Dina Fitria (JURNAL TELISKA, 2025)
Room temperature and humidity in tropical climates, such as in Indonesia, are generally controlled using air conditioning (AC), which has now become a basic necessity. This study aims to improve the durability and energy efficiency of air conditioning systems through the application of microcontroller-based devices. Monitoring is carried out by measuring the AC electrical current, where the normal value is in the range of 3.2–3.6 amperes, while when the current exceeds 4 amperes, the system automatically cuts off the electricity supply. In addition, a water level control sensor with a maximum limit of ±4 cm is installed on the inner water tank. If the water level reaches ±3 cm and touches the sensor, the system will automatically stop the AC operation. To support remote monitoring, the system is equipped with an Arduino NodeMCU ESP-32 module integrated with the Blynk application, so that users receive notifications when a disturbance occurs. Real-time monitoring information is also displayed on the LCD screen on the control panel. The results of the study show that this design is able to provide protection against damage caused by excessive current and water levels, while also increasing the operational efficiency of the AC.